Developing 21st century graduate attributes: incorporating novel teaching strategies in a physiotherapy curriculum. (2nd July 2016) - Stewart, Jennie; Shanmugam, Sivaramkumar; Seenan, Christopher
Abstract: In the current economic climate employability, i.e. the acquisition of a range of knowledge, skills and attributes that support continued learning and career development, is high on the agenda for many higher education institutes (HEIs). Scottish HEIs have identified a set of generic attributes considered necessary for graduate employability in the twenty-first century. Teachers often assume students automatically master skills that enhance employability throughout their course, while the explicit teaching of generic attributes is difficult given already full programmes. This report describes the background to incorporating novel teaching strategies, aimed at increasing students' generic attributes, into the level 1 physiotherapy curriculum in a west of Scotland University. Eight Level 1 physiotherapy students participated in a focus group in order to ascertain issues of relevance and concern to the cohort, and ensure novel teaching strategies would be relevant to the needs of students on the programme. Thematic analysis was undertaken on the data, and three themes were identified reflecting the shared student experience: importance of peer feedback, perceptions of lack of knowledge, and low confidence levels. The three themes are discussed in relation to generic attributes, along with an overview of the strategies that were developed for implementation.